Ferromagnetic α-Fe2O3 NPs: a potential catalyst in Sonogashira–Hagihara cross coupling and hetero-Diels–Alder reactions. Issue 6 (29th October 2015) - Kataria, Meenal; Pramanik, Subhamay; Kaur, Navleen; Kumar, Manoj; Bhalla, Vandana
Abstract : Applications of in situ generated ferromagnetic α-Fe2 O3 NPs as an efficient and recyclable catalyst for carbon–carbon bond formation via Sonogashira–Hagihara coupling reactions and the synthesis of pyran derivatives by hetero-Diels–Alder reactions have been demonstrated. Abstract : Applications of ferromagnetic in situ generated α-Fe2 O3 NPs as an efficient and recyclable catalyst for carbon–carbon bond formation via Sonogashira–Hagihara coupling reactions and the synthesis of pyran derivatives by hetero-Diels–Alder reactions have been demonstrated. This catalytic system is easily recoverable due to the ferromagnetic nature of α-Fe2 O3 NPs and can be reused with sustained selectivity and activity.